ANALISIS KEPEMIMPINAN, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA GURU SMK NEGERI 3 SUKOHARJO - Fikri Nurhuda; Sri Hartono; Burhanudin Ahmad Yani (Universitas Slamet Riyadi, 2020)
The purpose of this study was to determine the effect of teacher performance partially and simultaneously at SMK Negeri 3 Sukoharjo. The research used is quantitative research. The population in this study were all teachers who had taught at SMK Negeri 3 Sukoharjo with a population of 60 people, so this study was a population study. The F test results show that leadership, motivation and work discipline simultaneously and significantly influence the performance of teachers in SMK Negeri 3 Sukoharjo. While the test results show that leadership partially has a positive and significant effect on teacher performance, motivation has a positive and significant effect on teacher performance in SMK Negeri 3 Sukoharjo and work discipline also has a positive and significant effect on teacher performance at SMK Negeri 3 Sukoharjo.